PREDIKSI PENYEBAB KECELAKAAN LALU LINTAS DI JALAN LINTANG KABUPATEN ACEH TENGAH MENGUNAKAN METODE APRIORI - Richasanty Septima; Ira Zulfa; Muhammad Fajri (Universitas Gajah Putih, 2022)
The increasing number of traffic accidents from year to year requires serious attention and mitigation. Because considering that traffic accidents are a high enough killer factor. The dominant factor that causes the accident is difficult to know, because the driver's error factor is still the benchmark, especially on Jalan Lintang Kampung Kemili. Bebesen District, Central Aceh Regency. The Apriori method works by finding the frequent item set from a data stored in a large database. Aims to find out the dominant causes of traffic accidents. The basic idea of ​​the Apriori algorithm is to find a combination of items that meet the minimum requirements of the support value in the database. The support value of an item is obtained Frequent itemset which shows the itemset that has a frequency of occurrence more than the specified minimum value. The results of the multiplication between the support and confidence factors that caused accidents that often occurred during 2018 were caused by drivers under U (age) who often violated traffic and the physical condition of the drivers causing a high accident rate with a support value of 16% and a confidence value of 50%.